Environmental Theology: An Islamic Education Perspective at UIN Raden Intan Lampung - Firdaus Armansyah; Syaripudin Basyar; Ali Murtadho (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
In the Islamic perspective, humans are positioned as khalifah fil ardh (vicegerents on earth) who bear a theological responsibility to maintain environmental balance as part of a divine trust. Therefore, the development of environmental theology within Islamic education is essential for fostering ecological awareness grounded in the values of tauhid (monotheism), ethics, and moral responsibility. This study aims to analyze the concept of environmental theology from the perspective of Islamic education, examine its integration within the Islamic education system at UIN Raden Intan Lampung, and analyze the implementation of the Green Campus program as its practical manifestation. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that environmental theology is constructed upon five main principles: tauhid, khalifah, amanah (trust), justice (‘adl), and public benefit (maslahah). The integration of these values is realized through institutional policies, the development of environmentally-based curricula, and campus environmental management programs based on the Green Campus concept. This study recommends that future research employ quantitative or mixed methods approaches to measure the effectiveness of environmental theology implementation on students’ ecological behavior. In addition, comparative studies across universities, as well as exploration of the use of digital technology in strengthening the internalization of environmental theology values, are also needed.